Downstream of tyrosine kinase 1 and 2 play opposing roles in CD200 receptor signaling. - Mihrshahi, R; Brown, M (2010)
The CD200 receptor (CD200R) negatively regulates myeloid cells by interacting with its widely expressed ligand CD200. CD200R signals through a unique inhibitory pathway involving a direct interaction with the adaptor protein downstream of tyrosine kinase 2 (Dok2) and the subsequent recruitment and activation of Ras GTPase-activating protein (RasGAP). Ligand engagement of CD200R also results in tyrosine phosphorylation of Dok1, but this protein is not essential for inhibitory CD200R signaling in human myeloid cells. In this paper, we show that CD200R-induced phosphorylation of Dok2 precedes phosphorylation of Dok1, and that Dok2 and Dok1 recruit different downstream proteins. Compared with Dok2, Dok1 recruits substantially less RasGAP. In addition to binding RasGAP, Dok2 recruits the adaptor molecule Nck in response to ligand engagement of CD200R. CD200R-induced phosphorylation of Dok1 results in the recruitment of CT10 sarcoma oncogene cellular homologue-like (CrkL), whereas the closely related CT10 sarcoma oncogene cellular homologue interacts constitutively with Dok1. Knockdown of Dok1 or CrkL expression in U937 cells resulted in increased Dok2 phosphorylation and RasGAP recruitment to Dok2. These data are consistent with a model in which Dok1 negatively regulates Dok2-mediated CD200R signaling through the recruitment of CrkL.